EVALUASI SISTEM INFORMASI REKAM MEDIS PADA BAGIAN PENDAFTARAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DI RSJD Dr. RM SOEDJARWADI PROVINSI JAWA TENGAH - , ARDAN ARDIAN; , Nur Rokhman S.Si.,M. Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Regional mental hospital Dr. RM Soedjarwadi Central Java Province is a psychiatric hospital that has implemented information technology to improve quality of service. In November 2013, Regional mental hospital Dr. RM Soedjarwadi Central Java Province experienced a change of Hospital Management Information System (SIMRS) in which there are Medical Record System (SIRM) are used in the medical records of patients included in the registration service. The problems that occur due to changes SIRM certainly felt by the admissions officer that include the presence of missing data when editing patient data and SIRM functions that do not satisfy the needs of users. Since the first time system changed, the new SIRM has not been evaluated. Therefore, researchers are interested in knowing the use and understanding of the user associated with the Evaluation of Medical Record Information System (SIRM) at patient registration services which are used for consideration to the developer. Objective: To identify the overview and use the new SIRM on the registration of the medical records of Regional mental hospital Dr. RSJD. RM Soedjarwadi Central Java Province, Knowing the user's understanding of admissions officers on outpatient, inpatient, and emergency department in the receiving the new SIRM application based on the Technology Acceptance Model (TAM). Methods: This type of research is a descriptive study using a qualitative approach. The study design was cross-sectional. Data collection techniques in this study is the observation and interview Results: Medical Record Information System (SIRM) in Regional mental hospital Dr. RM Soedjarwadi Central Java province its have not been using the personal account officer that contains the username and password. Medical Record Information System in Regional mental hospital Dr. RM Soedjarwadi Central Java to easily because it meets the indicator convenience provided by Davis (1989) to study the ease, convenience in increasing skills, and ease of operation. SIRM in RSJD Dr. RM Soedjarwadi Central Java province have not been able to easily do what users want because there are activities on the enrollment of patients who can not be implemented as printing bills and placement of a menu that has not been as expected. SIRM in Regional mental hospital Dr. RM Soedjarwadi Central Java province is usefull in service patient enrollment because it meets the dimensions benefit from Chin and Todd (1995), which facilitates the work, beneficial, increase productivity, enhance effectiveness, and develop job performance.